Analisis Wacana Multimodal Pada Iklan Scarlet Whitening Versi Song Joong Ki Di Youtube - Artha Uli Silalahi; Refin Sianturi; Sania Sari Silalahi; Mustika Wati Siregar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The complexity of meaning in advertising involves not only elements of Language that play a role in conveying meaning but play a role in conveying meaning but also elements of nonverbal Language and other visual means. Therefore a visual approach is needed to understand complexity. This article discusses the visual analysis of scarlet Whineting's advertisement in collaboration with Song Joong Ki as a Brand Ambassador. Data analysis techniques use the concepts of Kress and Leeuwen's theory. The results of this study integrate aspects in scarlet whitening advertisements, Song Joong Ki's version of scharlet whitening advertisements succeeded in creating strong visual appeal, presenting products to beauty and forming socio-cultural values about beauty, especially in Indonesia-South Korea. This study used qualitative descriptive method.